Self-assembly Polyrotaxanes Nanoparticles as Carriers for Anticancer Drug Methotrexate Delivery - Zhang, Longgui; Su, Ting; He, Bin; Gu, Zhongwei (Nano-Micro Letters, 2014)
α-Cyclodextrin/poly(ethylene glycol) (α-CD/PEG) polyrotaxane nanoparticles were prepared via a self-assembly method. Anticancer drug methotrexate (MTX) was loaded in the nanoparticles. The interaction between MTX and polyrotaxane was investigated. The formation, morphology, drug release and in vitro anticancer activity of the MTX loaded polyrotaxane nanoparticles were studied. The results show that the MTX could be efficiently absorbed on the nanoparticles, and hydrogen bonds were formed between MTX and α-CDs. The typical channel-type stacking assembly style of polyrotaxane nanoparticles was changed after MTX was loaded. The mean diameter of drug loaded polyrotaxane nanoparticles were around 200 nm and the drug loading content was as high as about 20%. Drug release profiles show that most of the loaded MTX was released within 8 hours and the cumulated release rate was as high as 98%. The blank polyrotaxane nanoparticles were nontoxicity to cells. The in vitro anticancer activity of the MTX loaded polyrotaxane nanoparticles was higher than that of free MTX.